2013
DOI: 10.3747/co.20.1543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recurrence and Survival Rates after Breast-Conserving Therapy and Mastectomy in Young Women with Breast Cancer

Abstract: Multiple randomized trials have demonstrated that breast-conserving therapy with partial mastectomy and radiotherapy provides survival equivalent to that seen with mastectomy for patients with early-stage breast cancer. Breast-conserving therapy has been associated with better quality of life relative to mastectomy and has become the standard of care for patients with early-stage breast cancer. Young age has been identified as a risk factor for recurrence and death from breast cancer. Some studies have suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 20 publications
2
48
0
2
Order By: Relevance
“…Six randomized controlled trials comparing mastectomy and BCT all included a low proportion of young breast cancer patients (12-23%) [44], making it hard to draw any conclusion for this subgroup. Few cohort studies restricted to young breast cancer patients have been published [2,[45][46][47][48][49], and they are limited by the inclusion of a mixture of different TNM stages, by the variety of adjuvant systemic treatments offered, and by a median follow-up time of less than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Six randomized controlled trials comparing mastectomy and BCT all included a low proportion of young breast cancer patients (12-23%) [44], making it hard to draw any conclusion for this subgroup. Few cohort studies restricted to young breast cancer patients have been published [2,[45][46][47][48][49], and they are limited by the inclusion of a mixture of different TNM stages, by the variety of adjuvant systemic treatments offered, and by a median follow-up time of less than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the rates of breast cancer recurrence after BCT are nowadays similar to the rates of local recurrence seen after mastectomy. However, it has to be stated that the rates are obviously not identical; especially in younger patients, the discrepancy becomes evident [28,29]. On the one hand, based on a review of the available literature there is no definitive evidence that mastectomy provides a consistent recurrence-free survival or OS benefit over BCT.…”
mentioning
confidence: 93%
“…BCS followed by radiation treatment represents the standard of care in patients with early-stage breast cancer [8]. Several studies confirmed that this procedure shows equivalent survival rates (more than 20 years) compared to mastectomy [8][9][10]. Breast oncoplastic surgery (BOS) comprises the surgical excision of breast cancer that allows oncologically safe breast conservation and breast remodeling, reducing postoperative deformities [11][12][13].…”
Section: Introductionmentioning
confidence: 99%